Privilege and property essays on the history of copyright - Deazley, Ronan; Kretschmer, Martin, 1963-; Bently, Lionel, 1964- (OpenBook, 2010)
"What can and can't be copied is a matter of law, but also of aesthetics, culture, and economics. The act of copying, and the creation and transaction of rights relating to it, evokes fundamental notions of communication and censorship, of authorship and ownership--of privilege and property. This volume conceives a new history of copyright law as fifteen leading academics discuss the changing state of intellectual property across time and between countries"--Publisher's description.
Keywords: Copyright -- History.; LAW -- Intellectual Property -- Copyright.; Copyright.; Law; Aesthetics; Cultural studies; John Milton; Legal history; Copyright history; Copyright law; Creative commons; Patent; Intellectual property; Pubic domain; Book history; Censorship; Electronic books.; History.